Pengaruh Kedisiplinan dan Motivasi Terhadap Hasil Belajar Matematika Kelas Rendah Sekolah Dasar - Sari, Anggi Multi; Sukartono, Sukartono (Universitas Negeri Padang, 2024)
Discipline and motivation are one of the factors that can affect student learning outcomes. Based on the results of observations carried out at SD N Jetis 02, it show that these two things are not optimal and need to be improved. In this study, the aims were to (1) determine the effect of discipline on low-grade learning outcomes at SD N Jetis 02, (2) determine the effect of motivation on low-grade learning outcomes at SD N Jetis 02, (3) determine the effect of discipline and motivation on the learning outcomes of low-grade students at SD N Jetis 02. The method in this research is quantitative with a non-experimental design, with a total population of all low-grade students totalling 54 students with a sample of 35 calculated using the proportional random sampling formula. The research instrument used a questionnaire of 30 questions per variable X. Data collection techniques were used to discipline and motivational questionnaires as well as school documents in the form of first-semester PTS scores. Instrument tests used validity and reliability tests. The prerequisite test uses the normality test. and Test the simple linear regression hypothesis using the t-test, and multiple regression using the F test. The results show that (1) there is a significant influence of discipline on the learning outcomes of low-grade students at SD N Jetis 02 4.5%, (2) there is an influence of motivation significantly 10% on the learning outcomes of low-grade students at SD N Jetis 02, (3) there is a significant joint influence of discipline and motivation on the learning outcomes of low-grade students at SD N Jetis 02 for the 2021/2022 academic year with an effective contribution rate of 50% and 50% are given by variables that have not been examined from this study.